Twin delivery: incidence and perinatal outcome in a Nigerian mission hospital (Bangladesh Journal of Medical Science, 2011)
Background: The incidence of twin delivery in Nigeria may have changed, in view of the worldwide increase in the rates of twinning attributed to increasing maternal age and use of fertility therapies. Twin gestation is associated with increased risk of adverse perinatal outcome. Objective: To determine the current incidence of twin delivery in Benin City and document their perinatal outcome. Methods: A four-year cross-sectional study of twin deliveries in a Nigerian mission hospital was conducted. The perinatal outcome in 115 sets of twin was compared with that of 230 singleton controls. Results: The current incidence of twin delivery was 25.3 per 1000 deliveries or one in 40 births. Sex ratio was 0.98 : 1 in favour of females. The highest incidence was in the month of August while the lowest incidence was in the month of November (p